2014
DOI: 10.3402/edui.v5.24612
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration Index in Vocational Students – Dimensionality, Reliability, and Construct Validity

Abstract: The self-determination theory (SDT) distinguishes between intrinsic and extrinsic aspirations or life goals, which tend to fall into two separate constructs. The pursuit of intrinsic goals, relative to extrinsic ones, is associated with numerous cognitive, affective and behavioural outcomes that are considered to be positive for individuals as well as for society such as, for example, students' school persistence. Developed by SDT researchers, the Aspiration Index has been widely explored. However, it has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To fill the gap in the literature, the present study focuses on a concept from the second category, the value students attach to attainable goals or aspirations when pursuing education. It has been argued that students who highly value education show more persistence and less drop out (Utvaer et al 2014;Zava et al 2022). For instance, selfdetermination theory proposes that life goals or aspirations refer to the long-term aims people value and strive for, and are closely linked to the value they attach to education Ryan 1993, 1996;Utvaer et al 2014).…”
Section: Value Of Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…To fill the gap in the literature, the present study focuses on a concept from the second category, the value students attach to attainable goals or aspirations when pursuing education. It has been argued that students who highly value education show more persistence and less drop out (Utvaer et al 2014;Zava et al 2022). For instance, selfdetermination theory proposes that life goals or aspirations refer to the long-term aims people value and strive for, and are closely linked to the value they attach to education Ryan 1993, 1996;Utvaer et al 2014).…”
Section: Value Of Educationmentioning
confidence: 99%
“…It has been argued that students who highly value education show more persistence and less drop out (Utvaer et al 2014;Zava et al 2022). For instance, selfdetermination theory proposes that life goals or aspirations refer to the long-term aims people value and strive for, and are closely linked to the value they attach to education Ryan 1993, 1996;Utvaer et al 2014). Theoretically, students who attach more value to education are expected to exert more effort and make behavioral choices that lead to higher achievement (Massey et al 2008).…”
Section: Value Of Educationmentioning
confidence: 99%
“…The average of the item raw scores for each subscale were calculated and then summed to create an overall materialism score (Kasser & Ryan, 1996). This measure has shown strong psychometric properties (e.g., Grouzet et al, 2005;Kasser & Ryan, 1993, 1996Ryan et al, 1999;Schmuck et al, 2000;Utvaer et al, 2014) with testretest correlations in the range of 0.66 to 0.77 (e.g., Kasser et al, 2014), and Cronbach's alphas in the range of .60 to .89 (e.g., Kasser & Ryan, 1993, 1996Sheldon, 2005).…”
Section: Aspirations Indexmentioning
confidence: 99%
“…Intrinsic aspirations are related to personal growth and acceptance, emotional intimacy and affiliation, and community involvement; extrinsic aspirations are related to selfpromotion, financial success, social recognition, and having an appealing appearance. A variety of studies have found that individuals with strong extrinsic aspirations are more likely to be associated with negative indicators of mental health and well-being, whereas intrinsic aspirations have been found to predict positive outcomes (e.g., Niemiec, Ryan, & Deci, 2009;Romero, Gómez-Fraguela, & Villar, 2012;Ryan et al, 1999;Utvaer, Hammervold, & Haugan, 2014). Additionally, recent evidence indicates that intrinsic aspirations are positively associated with enhanced learning, performance, and persistence in school settings (Rumberger, 2011), as well as a variety of indicators of well-being, such as life satisfaction (Vansteenkiste, Duriez, Simons, & Soenens, 2006), self-actualization (Schmuck, 2001), and relationship quality (Kasser & Ryan, 2001).…”
Section: Aspirationsmentioning
confidence: 99%